Diversity of Functional Traits in Leaves of Syzygium Species in Lowland and Highland - Simanjuntak, Susan; Winarni, Endang Widi; Rahman, Wiguna; Kurniawan, Vandra; Normasiwi, Suluh (Jurnal Riset Biologi dan Aplikasinya, 2025)
Syzygium is a genus of Myrtaceae with 1,236 species. The functional traits of each species vary. The purpose of this study was to determine the variation in the functional traits of Syzygium leaves found in the lowlands and highlands. In this study, Syzygium leaves were collected from the Bogor Botanical Garden (lowland) for 27 species, while from the Cibodas Botanical Garden (highland) for 35 species. Ten parameters were measured, including leaf Fresh Weight (FW), leaf Dry Weight (DW), Leaf Area s(LA), Specific Leaf Area (SLA), Leaf Dry Matter Content (LDMC), Specific Leaf Weight (SLW), Chlorophyll Content (CC), Stomatal Density (SD), Stomatal Length (SL), and Stomatal Width (SW). Based on the results of the study, a diversity of functional traits in Syzygium species was observed in the lowlands and highlands. The results also indicated that the elevation influences variations in functional traits. Most of the leaf traits were found to be higher in the lowland species. Phenotypic plasticity of parameters was observed within the species found in both lowland and highland locations